Soft skills and their strategic role in employability - Boerchi, Diego; Ghisio, Silvia (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The labour market has been severely affected by the restrictions imposed by the pandemic. In Italy, the haemorrhaging of workers from companies has been prevented by a legislative intervention, which, however, cannot be maintained for long and, in any case, buffers and hides a dynamic with which many workers will soon have to reckon. It is not just a question of job losses, but of the need to rethink for a context that in the coming years will be profoundly different from the one that preceded the pandemic. Organisational processes have been redesigned in a very short time, and necessarily in an improvised way, to cope with an emergency situation, but in the future they will not go back to what they were in the past: they will be rethought in the light of new needs, but also of new willingness on the part of both companies and workers.